Synthesis of Modified Poly (glycidyl methacrylate) (PGMA) Hydrogels, and Investigation of Their Potential in Dye Removal - Kübra Gülcemal; Kutalmış Gökkuş (Turkish Journal of Agriculture: Food Science and Technology)
Anthropogenic activities with increasing population lead the pollution of ecosystems. Over one-third of the world's water resources are utilized for agricultural, domestic, and industrial activities, resulting in contamination by synthetic, and geogenic compounds such as dyes, fertilizers, pesticides, and heavy metals. Among these pollutants, dyes are particularly noteworthy due to their extensive use across various sectors, making them one of the leading contributors to water pollution. For this reason, dyes are one of the most important pollutants that cause water pollution. Therefore, the adsorption of Bromophenol blue (BPB) was studied in this study. Firstly, PGMA gels were produced by polymerizing of glycidyl methacrylate (GMA) monomer. Secondly, the PGMA gels were modified to prepare the new adsorbents for the adsorption of BPB dye. Thirdly, the adsorption of BPB dye was carried out. The batch adsorption method was used. The optimum adsorbent amount, initial BPB concentration, pH, and temperature parameters for PGMA gels were determined. The adsorption mechanism between modified PGMA gels, and BPB dye was elucidated by Langmuir, Freundlich, Dubinin-Radushkevich, and Temkin isotherm models. As a result, it was seen that modified PGMA gels showed good performance in the adsorption of BPB.